Healthy style / Wan Emir Hussein Wan Rahim, Muhammad Zikry Khuzairi and Nazzrudin Mohd Nawi - Wan Rahim, Wan Emir Hussein; Khuzairi, Muhammad Zikry; Mohd Nawi, Nazzrudin (2020)
Healthy Style is a business that can be categorized as Small Medium Enterprise (SME) which provide personal care products to customer. We are specialized in providing personal healthcare products that are combined with usage of technology. Healthy Style consists of three partnership. Through our long term research and observation, we had planned to set up this business as there is a huge prospect in this area of industry. Moreover, we have discovered that the demands of hand sanitizer has increased dramatically in recent years, especially during the COVID-19 pandemic. Apart from that we have been observed that there are fewer competitors that involved in providing wearable products. We take these opportunities to expand our business. Since our company is listed as a new company in the market, it is clear that there are many aspects that are needed to considering order for our company to market itself to everyday people. In conclusion, we hope that Healthy Style can be a well-known company throughout the nation and able to provide greater service, especially in areas of personal healthcare. We also believe demand of sanitisers will increase